Law and Society: Ethnicity and Social integration Through Norm Contestation - Malk, Bahlbi (Journal of Central and Eastern European African Studies, 2025)
Growing ethnic tensions, ethnic-based violence, and societal polarization are some of the current problems that contemporary communities around the globe are facing. However, while ethnicity has been weaponized to serve as a basis for political mobilization or counter-mobilization, neither ethnic difference nor ethnicity is the cause of tensions or violence as they have been portrayed to be. Ethnic-related violence is the consequence of politically driven naturalization and reification of ethnicity, the institutionalization of ethnic divisions, the ethnicization and racialization of social/group relations, and the ethnification of territories, cultures, and societies. Therefore, departing from the naturalists’ tendency of group relation dichotomization where ethnicity and race are perceived as distinct, pre-given, instinctual, tangible, bounded, static, and ancestrally linked singularity, this article argues that they should be conceptualized in relational, intersectional, processual, dynamic and multidimensional terms where “multiple diversity governance” and multi-level social integration is possible.